Perencanaan Pembangunan Jalan Sirtu Dan Bangunan Pelengkap Di Dusun III, Desa Oemasi, Kecamatan Nekamese, Kabupaten Kupang, Propinsi Nusa Tenggara Timur - Laurensius Embu Odjan; Soterdino D. Obe; Siprianus S. Senda (CV. Multi Kreasi Media, 2023)
Road development planning is a type of infrastructure development, which functions as a fulfillment of one of the community's needs. Road construction includes the process of opening traffic spaces to connect one area to another. Road construction aims to get comfortable, safe and economical roads for the people who use them. Thus, it makes it easier for road users to reach a location and produces a high level of comfort and safety. The construction of the sirtu road and complementary buildings in hamlet III, Oemasi Village will greatly assist the people in Oemasi Village to expedite the flow of distribution of goods and services and economic activities in Oemasi Village. This requires good planning. This prepared plan is a solution for the Oemasi Village government to build roads according to community needs with a transparent and accountable budget.